Pengaruh Harga Minyak Dunia Dan Makroekonomi Terhadap Pergerakan Indeks Harga Saham Gabungan (IHSG) Di Bursa Efek Indonesia (BEI) Periode 2018-2022 - Abdul Manaf Dientri; Novi Darmayanti; Radian Sri Rama (Universitas Islam Darul 'ulum Lamongan, 2024)
Abstract This study aims to determine the effect of world oil prices and macroeconomics on the movement of the Jakarta Composite Index (IHSG) on the Indonesian Stock Exchange (IDX) for the 2018-2022 PERIOD. By using the multiple linear regression analysis method, it can be seen how the relationship between world oil and macroeconomic variables as independent variables with the composite stock price index variable as the dependent variable. The data used in this study is monthly data for all variables in the 2018-2022 period. Then from the research results it was found that the world oil price variable and the inflation variable had a positive and significant effect on the JCI. The exchange rate variable has a negative and significant effect on the JCI. While the interest rate variable has no effect on the JCI variable partially..